Effects of Cordyceps Militaris and Cordyceps Sinesus on nursery pig performance - Richert, Jacob A. (Kansas State University, 2019)
Cordyceps Militaris is a human therapeutic food with many bioactive compounds with antimicrobial and antiviral activities. There is little research in feeding this mushroom powder (MP) to pigs, to evaluate its potential various levels and combinations were fed to nursery pigs. Experiment one used one-hundred sixty crossbred pigs ((Duroc × (York × Landrace)) (19.4 d of age; initial BW 7.24 kg), to test a previously reported dose to pigs and a human equivalent dose. One ppm proved to be too low of inclusion with identical performance to the NC, while 300 ppm had numerically improved performance over the NC and matched Carbadox’s performance in the final phase. Experiment two was a titration study to find the optimal level of inclusion for this Cordyceps product. As a potential alternative to Carbadox in nursery pig diets one-hundred sixty crossbred pigs (18.8 d of age; initial BW 5.94 kg) were used in a 35-day growth trial. At various points of the study, pigs fed the 300 ppm and the step-down mushroom powder treatments tended to have improved (P < 0.10) growth performance compared with those fed the NC diet. During Phase 4 of the study, pigs fed Carbadox had greater ADG (P < 0.02) and improved G:F (P < 0.09) over pigs fed the NC. However, overall (d 0-35) there were no differences among treatments (P > 0.05). Experiment three evaluated the independent and additive effects of Cordyceps MP and Carbadox to pharmacological copper+zinc. Two hundred-ten crossbred weanling pigs (19 d of age; initial BW 5.8 kg) were used in a 33 day growth trial. Pigs fed the PC, PC+MP and CuZn treatment had increased BW (P<0.05), ADG (P<0.05), ADFI (P<0.10) and G:F (P<0.05) over the NC for phases 1, 2, and 3, with MP treatment being intermediate. During Phase 4, pigs fed MP, PC, MP+PC, and CuZn diets all had increased ADG (P<0.05; 455, 476, 504, 487, 431 g/d) and ADFI (P<0.05) over the NC pigs. Experiment four utilized one-hundred thirty two weanling pigs (18.2 d of age; initial BW 5.77 kg) for a 35 day growth trial to evaluate mushroom Beta-Glucans (BG) and MP. During Phase 1 (d 0-7) PC pigs had increased ADG, ADFI, and d7 BW (P < 0.05) over NC, pigs fed BG + MP also had increased ADFI in Phase 1 over the NC (P < 0.05). During Phase 2 and 3 (d 7-21) an illness affected the pigs. This has led to inconsistent performance because of pigs eating, but losing weight. In phase 4 there was a difference in BG and MP diets, with an interaction between source and dose of the MP and BG. The 300 level of MP improved feed efficiency, while the 300 level of BG reduced efficiency in phase 4. On average across all of the experiments the Cordyceps MP and BG improved nursery growth performance above NC and provided a portion of the antimicrobial treatment response.
Keywords: Mushroom Nursery Pig